Targeting anticorruption interventions at the front line: Developmental governance in health systems - Hutchinson, Eleanor; Naher, Nahitun; Roy, Pallavi; McKee, Martin; Mayhew, Susannah H; Ahmed, Syed Masud; Balabanova, Dina (BMJ Journals, 2022)
This article was published in BMJ Global Health by BMJ Journals [© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2020-003092_091 The Journal's website is at: https://gh.bmj.com/content/5/12/e003092